Pengaruh Debt to Equity Ratio, Return on Asset, dan Earning per Share terhadap Price to Book Value pada PT Bank Central Asia Tbk Periode 2014-2023 - Robiyatun Robiyatun; Diana Riyana Harjayanti (Ilmu Sosial, Ekonomi, dan Humaniora, 2024)
This research aims to determine the partial or simultaneous influence of the variables Debt to Equity Ratio (DER), Return on Assets (ROA), and Earnings Per Share (EPS) on Price Book Value (PBV). The population used in this research are all financial reports of PT Bank Central Asia Tbk for the 2014 - 2023 period and the samples come from financial statement position, profit and loss reports, stock overviews for 2014 - 2023. The type of research method used in this research is explanatory research with quantitative methods . Namely descriptive statistics of ratios. The research results show that the Debt to Equity Ratio has a tcount of 0.600 with a positive direction < ttable 2.30600 and a significant value of 0.571 > 0.05. So, personally, the Debt to Equity Ratio has no effect and is not significant on the Price Book Value. Return On Assets has a tcount of 1.539 with a positive direction < ttable 2.30600 and a significant value of 0.175 > 0.05. So that partially Return On Assets has no effect and is not significant on Price Book Value. Earning Per Share has a tcount of -2.444 with a negative direction < ttable 2.30600 and a significant value of 0.05 > 0.05. So in partial terms it can be interpreted that Earning Per Share has no effect and is not significant on Price to Book Value. Fcount is 4.068 < Ftable value of 4.76 with a significance value of 0.068 > 0.05. Thus, it can be concluded that simultaneously Debt to Equity Ratio, Return on Assets, and Earning Per Share have no effect and are not significant on Price to Book Value. And also the coefficient of determination (Adjusted R Square) is 0.506 or 50.6 percent and the remaining 49.4 percent is influenced by other variables outside the research model. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh secara parsial maupun secara simultan variabel Debt to Equity Ratio (DER), Retrun on Asset (ROA), dan Eaening Per Share (EPS) Terhadap Price Book Value (PBV). Populasi yang digunakan dalam penelitian ini adalah semua laporan keuangan PT Bank Central Asia Tbk Periode 2014 – 2023 dan sampelnya berasal dari posisi laporan keuangan, laba rugi, ikhtisar saham tahun 2014 – 2023. Jenis metode penelitian yang digunakan dalam penelitian ini adalah penelitian eksplanatori dengan metode kuantitatif. Yaitu statistik deskriptiv dari rasio – rasio. Hasil penelitian menunjukan Debt to Equity Ratio memiliki thitung 0.600 dengan arah positif < ttabel 2,30600 dan nilai signifikan  sebesar 0,571 > 0,05. Sehingga secara persial Debt to Equity Ratio tidak berpengaruh dan tidak signifikan terhadap Price Book Value. Return On Assets memiliki thitung 1,539 dengan arah positif < ttabel 2,30600 dan nilai signifikan sebesar 0,175 > 0,05. Sehingga secara persial Return On Assets tidak berpengaruh dan tidak signifikan terhadap Price Book Value. Earning Per Share memiliki thitung -2,444 dengan arah negatif < ttabel 2,30600 dan nilai signifikan 0,05 >0,05.Sehingga secara persial dapat diartikan Earning Per Share tidak berpengaruh dan tidak signifikan terhadap Price to Book Value. Fhitung sebesar 4,068 < nilai Ftabel sebesar 4,76 dengan nilai signifikasi sebesar 0,068 > 0,05. Dengan demikian maka dapat disimpulkan bahwa secara simultan Debt to Equity Ratio, Retrun on Asset, dan Earning Per Share tidak berpengaruh dan tidak signifikan terhadap Price to Book Value. Dan juga hasil nilai koefisien determinasi (Adjusted R Square) sebesar 0,506 atau 50,6 persen dan sisanya 49,4 persen dipengaruhi oleh variabel lain di luar model penelitian. Kata Kunci: debt to equity ratio; retrun on asset; earning per share; price to book value